2021
DOI: 10.3389/fnmol.2021.532291
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Horn Syndrome as a Result of Splice Site Mutations in ATP7A. No Activity of ATP7A Splice Variants Missing Exon 10 or Exon 15

Abstract: Disease-causing variants in ATP7A lead to two different phenotypes associated with copper deficiency; a lethal form called Menkes disease (MD), leading to early death, and a much milder form called occipital horn syndrome (OHS). Some investigators have proposed that an ATP7A transcript missing exon 10 leads to a partly active protein product resulting in the OHS phenotype. Here, we describe an individual with OHS, a biology professor, who survived until age 62 despite a splice site mutation, leading to skippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Analysis of RNA from V:2 showed a higher proportion of canonical ATP7A transcripts (13.9 %) compared to the cases reported previously ( Yasmeen et al, 2014 ; Møller et al . ), with the majority of the non-canonical transcripts featuring exon 5 skipping, rather than pseudoexon inclusion, as a result of the ATP7A c.1544-872C>G variant.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Analysis of RNA from V:2 showed a higher proportion of canonical ATP7A transcripts (13.9 %) compared to the cases reported previously ( Yasmeen et al, 2014 ; Møller et al . ), with the majority of the non-canonical transcripts featuring exon 5 skipping, rather than pseudoexon inclusion, as a result of the ATP7A c.1544-872C>G variant.…”
Section: Discussioncontrasting
confidence: 56%
“…The proportions of canonical transcripts in the less severely affected patients were 11 % and 2 %, suggesting that the proportion of canonical transcripts required to prevent the onset of the severest phenotypes lies below a 2 % threshold. This hypothesis was supported by the subsequent investigation of five patients with splice-site variants leading to exon skipping ( Møller et al .). In one patient with Menkes disease, 0.5 % of transcripts were canonical, which increased to 3.5 % canonical transcripts in patents with OHS.…”
Section: Discussionmentioning
confidence: 80%
“…Menkes is an infantile, fatal, inherited copper deficiency characterized by progressive neurological damage that eventually causes death. A mild form of Menkes disease is called occipital angle syndrome (OHS) ( Moller et al, 2021 ; Yasmeen et al, 2014 ), which showed a symptom of exophytic bone warts ( De Feyter et al, 2023 ) that is similar to the bony core of the horn. So we suspect ATP7A can have an important role in the ovine horn.…”
Section: Introductionmentioning
confidence: 99%